Air Conditioning System Using Vechile Suspension - R. , Hariharan; I. , Aburarul Haq; R. , Arun Kumar; E., Balaji; M. , Barath Kumar (International Journal of Psychosocial Rehabilitation, 2024)
In this project, we are collecting air cylinders and storing this energy in the compressor tank as a nonconventional method by simply driving the vehicle. A non-conventional energy system is very essential at this time to our nation. Compressed air production using a vehicle suspensor needs no fuel input power to produce the output of the air. For this project, the conversion of the force energy into air. The control mechanism carries the air cylinder (vehicle suspension), quick exhaust valve, non-return valve, and spring arrangement. Then this compressed air is passed to the heat exchangers. That is used to convert the heated air into cold air. Cold air is passed to the vehicle. The conventional vehicle suspension dissipates the mechanical energy, i.e., potential and kinetic energy. In spring, potential energy is stored and kinetic energy is wasted. The aim of this paper is that this wasted energy is compressed by using a single-acting cylinder in proper arrangement. The main aim of this paper is the compressed air production using vehicle suspension given to the air conditioning system. The pushing power is converted into compressed air energy by proper arrangement. The pneumatic single-acting cylinder is used for this project to compress the air. The output air from the pneumatic cylinder is collected through the quick exhaust valve and non-return valve, and this compressed air is stored inside the storage tank. After this research, we concluded that in a car there is a lot of fuel burned only for working of the A.C. while driving the car. If A.C. will run on another system rather than fuel, then there is lot of fuel saved in car, hence the efficiency of car will also increase